Evaluasi Pemanfaatan Media Pembelajaran pada Mata Pelajaran PAI di MTs Daruttaqwa Gresik - Nur Silva Nabila (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2020)
Learning media evaluation aims to find out whether the effectiveness and efficiency of the media used in conveying learning content. Weaknesses and strengths of a media will be known by this program, whether the media needs to be improved or not. This article discusses the use of instructional media in PAI subjects at MTs Daruttaqwa with descriptive deductive and inductive analysis. Sources of data derived from literature, observation, and interviews were analyzed qualitatively. The purpose of this article is a) to find out the learning media used in MTS Daruttaqwa b) to find out the use of learning media in MTs Daruttaqwa c) to analyze the evaluation of learning media in MTs Daruttaqwa. The conclusions of this article are a) The media used in PAI learning at MTs Daruttaqwa in the form of technology-based media such as language labs, computer labs, projectors and manual-based media such as props for example paper that contains a collection of pieces of verses of the Koran in Qur'an Hadith and other subjects b) Media used in PAI learning in MTs Daruttaqwa in the form of technology-based media and manual-based media c) PAI learning media in MTs Daruttaqwa is only limited to teaching aids for teachers and not as something that needs and much needed in learning activities